2019
DOI: 10.1111/anu.12897
|View full text |Cite
|
Sign up to set email alerts
|

Aurantiochytrium sp. meal can replace fish oil in practical diets for the juvenile Pacific white shrimp

Abstract: This study evaluated the use of microalgae (Aurantiochytrium sp.) meal as a substitute for fish oil in the diet of juvenile Pacific white shrimp (Litopenaeus vannamei) reared in a clear‐water system. Dietary treatments at five replacement levels (0%, 25%, 50%, 75%, 100%) were performed in triplicate. After 46 days, only a slight difference in shrimp final weight was observed among treatments (0.61 g). An increase in final weight was observed with replacement of up to 50% fish oil for microalgae meal, while the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…The authors noted an improvement in growth with increasing inclusion level of the Aurantiochytrium SCO as well as increase in the DHA content of the lipids of the shrimp muscle. Another recent study also reported the use of an Aurantiochytrium SCO as a source of n-3 fatty acids in the diet for Pacific white shrimp [132]. Similarly, these authors found that the inclusion of the microalgal SCO improved growth of the shrimp when included at 40 g/kg in the diet, replacing about 50% of the fishoil.…”
Section: Shrimpmentioning
confidence: 79%
See 1 more Smart Citation
“…The authors noted an improvement in growth with increasing inclusion level of the Aurantiochytrium SCO as well as increase in the DHA content of the lipids of the shrimp muscle. Another recent study also reported the use of an Aurantiochytrium SCO as a source of n-3 fatty acids in the diet for Pacific white shrimp [132]. Similarly, these authors found that the inclusion of the microalgal SCO improved growth of the shrimp when included at 40 g/kg in the diet, replacing about 50% of the fishoil.…”
Section: Shrimpmentioning
confidence: 79%
“…The use of microalgal SCP and SCO has been particularly active in shrimp nutrition and has been examined in a range of studies in the past decade [124][125][126][127][128][129][130][131][132][133][134].…”
Section: Shrimpmentioning
confidence: 99%
“…Many studies demonstrate that the correct use of the dose/ response ratio of immunostimulants improves the immune system of crustaceans, resulting in higher resistance to pathogens and stressors (Huang et al, 2006;Yangthong et al, 2016;Kitikiew et al, 2017). One example is the inclusion of algae which, due to its high nutritional value in terms of fatty acids and amino acids, improves the immune response, nutrient absorption and growth (Schleder et al, 2017;Guimarães et al, 2019). Nonwachai et al (2010) demonstrated a significant effect on the immune response of shrimp fed diets supplemented with seaweed rich in DHA and ARA (arachidonic) fatty acids.…”
Section: Zootechnical Parametersmentioning
confidence: 99%
“…This species is classified as an oleaginous microorganism due to its lipid production potential (Chi et al, 2009). Guimarães et al (2019), observed that the total substitution of fish oil (cod liver) with meal from Aurantiochytrium sp. added DHA to L. vannamei muscle.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research on Spirulina ‐fed shrimp showed that the highest final weight when the fish meal was partially replaced by Spirulina platensis in the diet of juvenile Pacific white shrimp (Hanel, Broekman, de Graaf, & Schnack, ). Guimarães et al () successfully replaced fish oil by Aurantiochytrium sp. meal in the diet of juvenile L. vannamei with no adverse effects after total replacement of dietary fish oil and increased level of DHA in shrimp muscle.…”
Section: Introductionmentioning
confidence: 99%